If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-2-x-4x=-3x+16
We move all terms to the left:
8x-2-x-4x-(-3x+16)=0
We add all the numbers together, and all the variables
3x-(-3x+16)-2=0
We get rid of parentheses
3x+3x-16-2=0
We add all the numbers together, and all the variables
6x-18=0
We move all terms containing x to the left, all other terms to the right
6x=18
x=18/6
x=3
| 5l+9=7l-23 | | 11x-(-5)=95 | | x^2-7x=x-13 | | 5x-2(4x+3=9 | | 23=4/6x | | -1/3=h/4-10/3 | | x^-7x=x-13 | | 9-x+5-3x=-1 | | 2n+3n+7=-21 | | 4(4x+5)=21x+18-5x+2 | | 10-2x=3.8x-16+3.8x | | -12/3w=-5 | | d+12=20 | | 7=3(x+0)-7 | | 4p+2p=6 | | 0.08x-2000/(x^2)-0.01=0 | | 374=2(10w)+2w | | 16=2(x+4)+8 | | 52=p-(3) | | 11y-8=9y+4 | | -13(4d-11)=18-5d | | 11y-8=9+4 | | 3h=7(0.2-0.42h)-10 | | 1k+10=-4-10 | | 5.4g+5=1.4g+17 | | 6.7g+10=2.7g+30 | | 81=3x=15 | | -2v+7(7v-5)=153 | | 4-5w=-3w | | 4x+5=7x−11 | | -26m=13 | | 176=8(1+7a) |